Melissopalynological Analysis of Honey from French Guiana - Weiwen Jiang; Marie-José Battesti; Yin Yang; Élodie Jean-Marie; Jean Costa; Didier Béreau; Julien Paolini; Jean-Charles Robinson (Foods, 2024)
Beekeeping directly depends on the floral biodiversity available to honey bees. In tropical regions, where nectar and pollen resources are numerous, the botanical origin of some honey is still under discussion. A precise knowledge of plants foraged by honey bees is useful to understand and certify the botanical origin of honey. In this study, attention was paid to honey samples from the French Guiana Atlantic coast where beekeepers generally place their hives in four types of biotopes: seaside vegetation, mangrove, savannah, and secondary forest. Pollen analysis of 87 honey samples enabled the identification of major plants visited by Africanized honey bees during the dry season (approximately from July to January). Through melissopalynologic analysis, 51 pollen types were identified and classified according to their relative presence. Frequently observed pollens (with relative presence > 50%) in French Guiana kinds of honey were those from Mimosa pudica, Cocos sp., Rhyncospora sp., Avicennia germinans, Paspalum sp., Spermacoce verticillata, Tapirira guianensis, Cecropia sp., Myrtaceae sp., Mauritia flexuosa sp., Solanum sp., and Protium sp. In many honeys, only M. pudica was over-represented (relative frequency > 90%). Color and electrical conductivity in French Guiana honeys exhibit significant variations, with color ranging from 27 mm to 110 mm Pfund, and electrical conductivity ranging from 0.35 to 1.22 mS/cm.